2004
DOI: 10.1097/01.mnm.0000130242.29692.b2
|View full text |Cite
|
Sign up to set email alerts
|

Low failure rate of fixed administered activity of 400 MBq 131I with pre-treatment with carbimazole for thyrotoxicosis: the Gateshead Protocol

Abstract: Our observations show that withholding an antithyroid drug in excess of just over 2 weeks prior to administering a fixed administered activity of radioiodine in patients with thyrotoxicosis leads to the lowest reported failure rate, irrespective of the underlying cause. One possible mechanism for this could be the avoidance of drug induced radio-resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
0
7
1
3
Order By: Relevance
“…Moreover, in contrast to previous reports, the negative effect of carbimazole on radioiodine therapy was con- firmed not only biochemically but also clinically, as quantified by the Crooks-Wayne score. Previous reports have indicated that the success of radioiodine treatment is not diminished if carbimazole is discontinued for 16 days [6], 5 days [7] or 5 to 3 days [8] before administration of radioiodine. However, even merely 5 days of withdrawal can lead to aggravation of hyperthyroidism [9], which is especially of concern in patients with severe concomitant diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in contrast to previous reports, the negative effect of carbimazole on radioiodine therapy was con- firmed not only biochemically but also clinically, as quantified by the Crooks-Wayne score. Previous reports have indicated that the success of radioiodine treatment is not diminished if carbimazole is discontinued for 16 days [6], 5 days [7] or 5 to 3 days [8] before administration of radioiodine. However, even merely 5 days of withdrawal can lead to aggravation of hyperthyroidism [9], which is especially of concern in patients with severe concomitant diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies have merged patients on diverse antithyroid drugs, namely thiamazoles and thiouracils, which have distinct detrimental effects on radioiodine treatment [20]. The influence of carbimazole alone on radioiodine treatment has been investigated in only a few reports [3][4][5][6][7][8], in which low success rates of radioiodine therapy with concomitant carbimazole treatment have exclusively been associated with significantly lower radioiodine uptake under carbimazole [3,5]. Generally, low radioiodine uptake is assumed to adversely affect the success of radioiodine therapy [12,13], although the opposite effect has also been reported [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(40) evidenciaram maior chance de remissão nos pacientes com menor RAIU nas 24 h (40). Além disso, em um outro estudo recente, não se observou diferença na resposta terapêutica ao 131 I em pacientes com RAIU nas 24 h entre 11 e 30% ou maior que 30% (41).…”
Section: Radioiodoterapia Em Doenças De Gravesunclassified
“…A total dose of 20 mCi achieves thyroid ablation in almost all patients and results in permanent hypothyroidisms in 75-90% of patients. 51 The incidence of post radioiodine hypothyroidism in first year is 25% and steadily increases thereafter at a rate of 5% per year. When required, the second dose of radioiodine should be given at least 6 months after the first dose.…”
Section: Radioiodinementioning
confidence: 99%